2n-3(4n+5)=-6+17

Simple and best practice solution for 2n-3(4n+5)=-6+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n-3(4n+5)=-6+17 equation:


Simplifying
2n + -3(4n + 5) = -6 + 17

Reorder the terms:
2n + -3(5 + 4n) = -6 + 17
2n + (5 * -3 + 4n * -3) = -6 + 17
2n + (-15 + -12n) = -6 + 17

Reorder the terms:
-15 + 2n + -12n = -6 + 17

Combine like terms: 2n + -12n = -10n
-15 + -10n = -6 + 17

Combine like terms: -6 + 17 = 11
-15 + -10n = 11

Solving
-15 + -10n = 11

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -10n = 11 + 15

Combine like terms: -15 + 15 = 0
0 + -10n = 11 + 15
-10n = 11 + 15

Combine like terms: 11 + 15 = 26
-10n = 26

Divide each side by '-10'.
n = -2.6

Simplifying
n = -2.6

See similar equations:

| 2(x-7)=15 | | 4x-2[2-3(3-5x)]=1 | | 4x-2[2-3(3-4x)]=1 | | 2(3x-7)+4=10 | | -7y+3+8y=12-20 | | 2(6x-5)(4x+5)=0 | | -5-5=0 | | 3+log^4(2x+6)=6 | | -16=-2(3+x) | | (-4i)(6i)=0 | | x+2=-2x+14 | | 4(2n-3)=(5n+4)+3 | | [2x+5]=14 | | 20=-36x-4(-6-2) | | 4-(7y-5)=6y-4 | | -16x^2+50x+15=0 | | (ax+by)(cx+y)=x | | 20x+5=21x-5 | | 20x=21x | | 80=(10+30p)-(150+20p) | | 10a+7=6a+10+3a | | 6(2x-7)+4=12x-38 | | -8u+30=2u | | x+3=-4x+23 | | 16x^2+50x+15=0 | | 18-(1/22)(2x)=9-(1/22)(x) | | (4x+5)(5x-1)=0 | | 2x+0.5x=770 | | log^2(x-1)=4 | | (2/3)(x+4)=(3/8)(x-3) | | 3x-8=4x-25 | | 6.1w+2.2=0.5w-3.4 |

Equations solver categories